Downregulation of CAMK2N1 due to DNA Hypermethylation Mediated by DNMT1 that Promotes the Progression of Prostate Cancer. (30th January 2023) - Peng, Wei; Feng, Huan; Pang, Linhao; Zhang, Junfeng; Hao, Yi; Wei, Xian; Xia, Qidong; Wei, Zhewen; Song, Wen; Wang, Shaogang; Liu, Jihong; Chen, Ke; et al.
Abstract : Calcium/calmodulin-dependentprotein kinase II inhibitor I (CAMK2N1) as one of the tumor suppressor genes is significantly downregulated in prostate cancer (PCa). Reduced expression of CAMK2N1 is positively correlated with PCa progression. However, the mechanisms of CAMK2N1 downregulation in PCa are still unclear. The promoter region of CAMK2N1 contains a large number of CG loci, providing the possibility for DNA methylation. Consequently, we hypothesized that DNA methylation can result in the reduced expression of CAMK2N1 in PCa. In the presented study, the DNA methylation level of CAMK2N1 in prostate cells and clinical specimens was determined by bisulfite sequencing (BS), pyrosequencing, and in silico analysis. Results showed that CAMK2N1 was highly methylated in PCa cells and tissues compared to normal prostate epithelial cells and nonmalignant prostate tissues, which was associated with the clinicopathological characteristics in PCa patients. Afterwards, we explored the expression of CAMK2N1 and its DNA methylation level by qRT-PCR, western blot, BS, and methylation-specific PCR in PCa cells after 5-Aza-CdR treatment or DNMT1 genetic modification, which demonstrated that the reduced expression of CAMK2N1 can be restored by 5-Aza-CdR treatment via demethylation. Moreover, DNMT1 formed a positive feedback loop with CAMK2N1 in PCa cells. The expression of CAMK2N1 was downregulated by DNMT1-mediated DNA methylation, which reversely induced DNMT1 expression through activating AKT or ERK signaling pathway. Finally, functional assays including wound healing, invasion, and migration assay, as well as the xenograft model in nude mice indicated that CAMK2N1 inhibited the invasion, migration, and proliferation of PCa cells and these effects were reversed by DNMT1 overexpression. In conclusion, DNMT1-mediated hypermethylation of CAMK2N1 not only downregulates the gene expression but also promotes the progression of PCa.